Alvarado Score: A Promising Tool in Diagnosis of Acute Appendicitis - Adhikari, Bimarsh (Journal of Nepalgunj Medical College, 2022)
Introduction: Appendicitis is the inflammation of vermiform appendix, one of the most frequent diagnoses for emergency department visits, resulting in hospitalization. Accurate and prompt diagnosis of acute appendicitis may reduce the incidence of morbidity and mortality resulting from perforation and other gravid complications. Aims:To evaluate the effectiveness of Alvarado scoring system in preoperative diagnosis of acute appendicitis. Methods: The study of 100 patients attending to Nepalgunj Medical College and Hospital during the year August 2021 to July 2022, with symptoms of acute appendicitis were included. The Alvarado score for each patient was evaluated. All the subjects included were scheduled for open appendicectomy and the specimens were subjected for histopathological evaluation. Patients with score less than 7 were categorized as Group A, whereas greater than 7 were categorized as Group B. Results: Among 100 patients, there were 58 males and 42 females. Symptoms like pain in right iliac fossa (97%), nausea and vomiting (85%) and anorexia (41%) were common. Positive signs were tenderness in right iliac fossa (92%) and fever (53.5%) with leukocytosis (73%) and neutrophilia in 62 cases (88%). Of 100 patients 27 belonged to Group A, whereas 73 belonged to Group B. 17 patients out of 27 in Group A were diagnosed with acute appendicitis on histology, whereas, 10 showed negative results. 69 out of 73 subjects in Group B were diagnosed with acute appendicitis on histology, whereas 4 showed negative results on histology. The rate of negative appendectomy was significantly higher in group A than group B. The overall sensitivity, specificity, positive predictive value, negative predictive value were 80.20%, 71.42%, 84.52% and 37.03% respectively. Conclusion: The Alvarado score when more than 7 enables risk determination in patients presenting with abdominal pain, linking the probability of appendicitis.